2003
DOI: 10.1021/np020497l
|View full text |Cite
|
Sign up to set email alerts
|

Three New Cytotoxic Sesterterpenes from a Marine Sponge Spongia sp.

Abstract: Three new sesterterpenes (1-3) were isolated from a marine sponge of the genus Spongia, and their structures were determined on the basis of spectroscopic analysis. The compounds 1-3 exhibited cytotoxicity against HeLa cells with IC(50) values of 19.5, 15.0, and 5.3 microg/mL, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 15 publications
(27 reference statements)
3
32
0
Order By: Relevance
“…The structural assignments of 8 were based on an accurate study of the 1D and 2D (COSY, HMQC, HMBC) NMR spectra. The 1 H and 13 C NMR spectral data of 8 were consistent with the data for 12-episcalarin 18,19 and suggested that 8 was a deacetyl derivative of 12-episcalarin and identical with the previously published 12-Odeacetyl-12-epi-scalarin which isolated from Spongia sp.…”
Section: Resultssupporting
confidence: 87%
“…The structural assignments of 8 were based on an accurate study of the 1D and 2D (COSY, HMQC, HMBC) NMR spectra. The 1 H and 13 C NMR spectral data of 8 were consistent with the data for 12-episcalarin 18,19 and suggested that 8 was a deacetyl derivative of 12-episcalarin and identical with the previously published 12-Odeacetyl-12-epi-scalarin which isolated from Spongia sp.…”
Section: Resultssupporting
confidence: 87%
“…Later, it has been found in the Tongan sponge Hyrtios erecta [28], in the sponge Spongia agaricina collected near Tarifa Island (Spain) [30], in a sponge Hyrtios sp. collected at American Samoa [32], in the sponges Hyrtios erecta collected at Setouchi (Japan) [75] and collected from Hainan Island in the South China Sea [76], in sponges of the genus Spongia collected at the Japan Sea [77,78] and collected at the South Sea of Korea [79], and in the nudibranch Chromodoris funerea collected at Kaibakku Lake, Palau [80]. 12-Epi-scalarin (85) 12-Epi-scalaradial, 5 PLA2 inhibition and antiinflammarory [25] 12-Epi-scalaradial, 5…”
Section: Pentacyclic Scalaranesmentioning
confidence: 99%
“…Antimicrobial [29] 12-Deacetyl-12,18-diepi-scalaradial, 10 Antitubercular, antimicrobial and cytotoxic [31,32] 12-Deacetyl-12,18-diepi-scalaradial, 10 Antifeedant [34,35] 12-Deacetyl-18-epi-12-oxoscalaradial, 11 Antimicrobial and cytotoxic [32] 12-Deacetyl-12-oxoscalaradial, 12 Ichthyotoxic [19] and antitubercular [31] 12-Deacetyl-12-oxoscalaradial, 12 Antimicrobial and cytotoxic [32] Mooloolabenes A (13), B (14) and C (15) Cytotoxic [36] Compounds RCE-protease inhibition and antitumour [68] epidermoid carcinoma KB, IC 50 = 18.5 μg/mL) [77], as well as neurotrophic activity in pheochromocytoma (PC-12) cells at the concentration of 50 μg/mL [78]. Compound 85 also showed inhibition of farnesoid Xactivated receptor (FXR) transactivation, which is related to potential drugs for hypercholesterolemia in humans, with IC 50 value of 60.4 μM [79].…”
Section: Pentacyclic Scalaranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 is a new addition to the Introduction Sesterterpenes are a large and diverse group of naturally occurring polyisoprene compounds found in plants, marine organisms and vertebrates [5]. Members of the family have moderate antibacterial activity against Mycobacterium tuberculosis strain H(37)Rv [28,29], anti-tumour activity and inhibit DNA replication [3] are cytotoxic against tumour cell lines [25] and have potent antiplasmodial properties [10].…”
mentioning
confidence: 99%